PENDIDIKAN KEWARGANEGARAAN MENGOPTIMALISASIKAN PEMAHAMAN PERBEDAAN BUDAYA WARGA MASYARAKAT INDONESIA DALAM KAJIAN MANIFESTASI PLURALISME DI ERA GLOBALISASI - Muhammad Mona Adha (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2015)
Pluralism in Indonesia is a wealth of experience to the citizens to be able to coexist in harmony. The main value of mutual respect and love between people is an important concern in Indonesia in the future to build a more cultured. Discourse of